Skupni trg Evropske unije - medsebojno priznavanje kvalifikacij poklica medicinske sestre in babice v Evrospki uniji - Požun, Peter (Obzornik zdravstvene nege, 2006)
After several processes of uniting, the European Union has become one of the largest markets. In the future, one of the most important factors of globalization will be open market for the free flow of people and above all, the possibility of employment in any of the member states. The right of employment is realized by the system of mutual recognition of diplomas and other professional qualifications. The use of directves and mutual recognitionof professional qualifications of regulated professions among member states enhances free flow of professionals in these countries. An European Union citizen has the right of recognition of professional qualifications in any of the member countries and the right to be employed - we are talking here about regulated professions. Among regulated professions, there is also the profession of nurse and midwife. On one side, the process ofacknowledgement of the profession is much simpler in the frames of the free flow in the whole European Union, while on the other side, the conditions of the profession involved in the care for public health and safety are much moredemanding.
Keywords: babice; Blennioidei; European Union; Evropska unija; medicinske sestre; poklicne kvalifikacije; skupni trg; zaposlovanje